A 1.36 μW 312–315 MHz synchronized-OOK receiver for wireless sensor networks using 65 nm SOTB CMOS technology. (March 2016) - Hoang, Minh-Thien; Sugii, Nobuyuki; Ishibashi, Koichiro
Abstract: The paper presents a receiver design operating at 312–315 MHz frequency band for wireless sensor networks. The proposed architecture uses synchronized on–off-keying (S-OOK) modulation scheme, which includes clock information together with data, providing self-synchronization ability for the receiver without a separate clock and data recovery circuit. In addition, a new technique is also proposed to reduce active time of the RF font-end for better energy efficiency. The receiver architecture is verified by using discrete RF modules and FPGAs, then VLSI design is carried out on 65 nm Silicon-On-Thin-Buried-Oxide (SOTB) CMOS technology and simulated using SPICE models to illustrate effectiveness of the proposed architecture. Post-layout simulation shows −58.5 dBm sensitivity with 1.36 μW and 8.39 μW power consumption corresponding to 10 kbps and 100 kbps data rate, respectively.